Answer:
[tex] L= x[/tex]
And the width for this case is:
[tex] W= 5x^3 +4 -x^2[/tex]
And we know that the perimeter is given by:
[tex] P= 2L +2W[/tex]
And replacing we got:
[tex] P(x) = 2x +2(5x^3 +4 -x^2)= 2x +10x^3 +8 -2x^2[/tex]
And symplifying we got:
[tex] P(x)= 10x^3 -2x^2 +2x+8[/tex]
Step-by-step explanation:
For this problem we know that the lenght of the rectangle is given by:
[tex] L= x[/tex]
And the width for this case is:
[tex] W= 5x^3 +4 -x^2[/tex]
And we know that the perimeter is given by:
[tex] P= 2L +2W[/tex]
And replacing we got:
[tex] P(x) = 2x +2(5x^3 +4 -x^2)= 2x +10x^3 +8 -2x^2[/tex]
And symplifying we got:
[tex] P(x)= 10x^3 -2x^2 +2x+8[/tex]